Pr??ticas de gest??o orientada ?? sustentabilidade no agroneg??cio no interior paulista: Inibidores e facilitadores para pequenos e m??dios produtores rurais - Caires, Ta??sa Cec??lia de Lima (2014)
Small and medium enterprises (SME s) play an important role in Brazilian s economy. Small and medium farmers also work under a lot of pressure to be more productive considering natural resources conservation, environmental protection and respect to people. This work intends to identify among small and medium farmers, which are the inhibitors and pushing elements for the adoption of more sustainability-oriented practices. This study also aims at identifying the practice of social and environmental management, comparing the characteristics of SMEs rural and non-rural and propose strategic guidelines to train small and medium farmers. The method used was a multiple case study, with six small and medium-sized farms in the state of S??o Paulo as units of analysis. The comparative analysis showed that rural small and medium farmers have, in general, poor education, adopt some management practices oriented to sustainability, and within the producers of sugarcane, there was evidence of loss of autonomy over management production because the industry is responsible for so. The interviewed farmers have an optimistic view about sustainability in their activities, adopt certain sustainability-oriented practices but often inefficient due to lack of guidance and knowledge on the topic. Management controls, when available, are very simple and do not have a systematic monitoring of results. Legal requirements are perceived as very important, however, they argue that bureaucracy and high costs for compliance will often make them unfeasible for business. Agricultural cooperatives play a fundamental role in the dissemination of technical knowledge and support to producers, being an important link in the value chain for disseminating a management model oriented to sustainability. It is proposed that the training for this audience should not hold extensive classroom Credit Hours, that the schedule should be suited to crop producers and count of technicians from the cooperative for "direct support" after training, in addition, the technical and pedagogical approach must be appropriate to this specific public in order to highlight the concrete benefits of the change of management model for your business.